Energy absorption characteristics of different volleyball court surfaces - Holthe, M.; Baker, A.; Hahn, M.; Gregg, M.; Pickney, D.; Fox, A.; Devries, S.; Derrick, T.; McLean, S. (1998)
One collegiate volleyball team who is the focus of this study has experienced an increase in lower leg injuries since training part time on a portable court surface. Several factors were identified that may play a role in this increased rate of injury: changes in intensity of training and training schedule, the increased use of ankle bracing systems during practice, changes in the landing kinematics on these different surfaces, and physical characteristics of the various playing surfaces including shock absorption and frictional characteristics. This study focused on the shock absorption characteristics of various court surfaces. A portable synthetic court (Sport Courtâ, Heartland Athletics, Inc., Normal, IL) was placed on three different surfaces (traditional wood flooring, a tartan flooring surface and artificial turf) and evaluated.